An assessment of hepatitis B vaccine introduction in India: Lessons for roll out and scale up of new vaccines in immunization programs - Chandrakant Lahariya; B P Subramanya; Stephen Sosler (Wolters Kluwer Medknow Publications, 2013)
Background: Hepatitis B vaccine was introduced in the Universal Immunization Program (UIP) of 10 states of India in the year 2007-08. This assessment was planned and conducted to ascertain the reasons for low reported coverage of Hepatitis B (Hep B) vaccine in comparison of similarly timed diphtheria, pertussis, and tetanus (DPT) vaccine; to identify operational and programmatic challenges in new vaccine introductions, and to derive lessons for further scale up of Hep B vaccination (or for introduction of any new vaccine) in UIP of India. Materials and Methods: Purposive sampling with both quantitative and qualitative data collection. Two districts each were purposively selected from 5 of the 10 states, which introduced Hep B vaccine, in the year 2007-08. A protocol was devised and data was collected through desk review, in-depth interviews and on-site observation at state, districts and facility levels. The assessment was completed in December 2009. Results: Coverage with three doses of Hep B vaccine was lower than similarly timed three doses of DPT vaccine. Poor stock management ("stock outs or nil stocks" at various levels), incomplete recording and reporting, perceived high cost & related fear of wastage of vaccine in 10 dose vial, and incomplete knowledge amongst health functionaries about vaccination schedule were the main reasons cited for reported lower coverage. Hep B vaccine birth dose was introduced in only 3 of 5 states evaluated. The additional reasons for low Hep B birth dose coverage were lack of knowledge amongst Health Workers about birth dose administration, no mechanism for recording birth dose, and insufficient trainings, official communications, and coordination at various levels. Conclusions: This assessment documents challenges faced in the introduction of hepatitis B vaccine in UIP in India and summarizes the lessons learnt. It is concluded that for successful introduction and scale up of any new vaccine in national or state immunization program; clear and timely central level instructions and oversight and improved stock management is required. At state and district levels; quality trainings, effective supervision and monitoring, improving data recording and reporting are key factor for success. The additional focus on Hep B birth dose administration may help in improving coverage. The lessons from this assessment can possibly be utilized for future introduction and scale up of any new vaccine (or other similar interventions) in India or in any other developing country setting.